(untitled) (IASH Indian Journal of Arid Horticulture, 2024)
Genetic variability parameters viz., GCV, PCV, heritability, genetic gain, mean performance and range were assessed among twelve varieties of onion during Kharif, 2023 with adopting randomized block design and three replications. Results revealed that phenotypic coefficient of variation were higher than corresponding genotypic coefficient of variation for all the traits studied and magnitude of various variability parameters were significantly differ among the genotypes studied. Highest heritability (98.95%) has been reported in fresh weight of bulb, followed by dry weight of bulb (98.83%) and neck diameter (96.64%). Bhima Dark Red was best performing variety on the basis of yield per ha, followed by Bhima Super and Bhima Red yielding 298.24, 279.64 and 266.84 q/ha, respectively.